Analisis Hubungan Perilaku Pemeliharaan Kesehatan Gigi dan Mulut Terhadap Status Kesehatan Gigi dan Mulut Siswa SD dan SMP di Medan - Sondang Pintauli (Jurnal Pendidikan dan Kebudayaan, 2010)
The purpose of this study was to analyze the relationship between oral health status (caries and periodontal status, oral hygiene) and oral health behavior of sixth grade primary and third grade of junior high school students in Medan. 393 children (197 primary school students and 196 junior high school students) were selected at cluster stratification. Dental caries and periodontal status of students was evaluated using the World Health Organization (WHO) diagnostic criteria. The oral hygiene of each child was assessed using the scoring of Simplified Oral Hygiene Index (OHI-S) from Greene and Vermillion. Interviews were conducted using a questionnaire to determine the oral health behavior of the children. The results showed that: 1) the caries prevalence of primary school children 92,39% with mean DMFT 3,42±2,36, and found higher in junior high school students 93,37% with mean DMFT 3,79±2,69. Junior high school students have >3 health sextants according to WHO. Almost all of students in both groups (50.8 and 52.6%) in moderate category; 2) 61.4% of the primary school students with good oral health habits while in junior high school students only 30.1%; 3) no statistically differences between oral health behavior and periodontal status (p>0.05), it was found significant differences between oral health behavior and caries experience and also oral hygiene (p<0.05). ABSTRAKPenelitian ini bertujuan untuk mengetahui hubungan perilaku pemeliharaan kesehatan gigi dan mulut terhadap status kesehatan gigi dan mulut siswa kelas VI SD dan III SMP di Kota Medan. Total sampel 393 orang yang diambil secara stratifikasi-klaster 2 tingkat, di mana siswa SD 197 orang dan SMP 196 orang. Pengambilan data dilakukan dengan wawancara dan observasi, serta uji statistik menggunakan one-way ANOVA. Hasil penelitian menunjukkan bahwa: 1) prevalensi karies siswa SD 92,39% dengan DMFT 3,42±2,36 dan meningkat pada siswa SMP menjadi 93,37% dengan DMFT 3,79±2,69. Siswa SMP mempunyai >3 sekstan sehat sesuai dengan target pencapaian gigi sehat WHO. Skor OHIS sebagian besar siswa SD dan SMP (50,8 dan 52,6%) pada kategori sedang; 2) 61,4% siswa SD mempunyai perilaku pemeliharaan kesehatan gigi yang baik, sedangkan pada siswa SMP hanya 30,1%; 3) terdapat hubungan yang signifikan antara perilaku pemeliharaan kesehatan gigi dengan skor pengalaman karies (DMFT) dan skor kebersihan mulut (OHIS) (p<0,05), sebaliknya tidak dijumpai hubungan yang signifikan antara perilaku pemeliharaan kesehatan gigi dengan status periodontal (p>0,05).